Primary meningitis due to Fusobacterium nucleatum successfully treated with ceftriaxone in a healthy adult male. (2019) - Hintze, Trager; Steed, Michelle; Sievers, Eric; Bagwell, John T.; Selfa, Nicola
Abstract: Fusobacterium nucleatum is a rod-shaped gram-negative obligate anaerobe; this organism, and other anaerobes, are usually not a part of the culture performed for a cerebrospinal fluid (CSF) sample. To date, four cases of Fusobacterium meningitis in adults have been published. We report successful treatment of a case of primary meningitis due to Fusobacterium nucleatum in an otherwise healthy 72-year-old male.